2011
DOI: 10.1007/s10591-011-9163-5
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Root of Relationship Attributions: Family-of-Origin Perspectives on Self and Partner Views

Abstract: A large body of research has been devoted to the study of family-of-origin (FOO) experience influences on future relationship outcomes and processes. In addition, substantial information exists regarding the role relationship attributions play in connection with relationship quality and stability. Yet, limited information has been forthcoming regarding how the FOO experience has an influence on attributions made in romantic relationships. Structural Equation Modeling (SEM) was employed to assess the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Given the substantial body of evidence that attributions are associated with relationship satisfaction, there is some confusion regarding underlying causes of specific attributions in romantic relationships. A number of researchers have demonstrated a link between adult attachment and attributions (Collins, Ford, Guichard, & Allard, ; Gardner, Busby, Burr, & Lyon, ; Mikulincer, , Study 2; Pearce & Halford, ). It is interesting that although Heene, Buysse, and Van Oost () found that attributions and adult attachment were linked to attributions and marital adjustment, they did not test whether attributions mediated the link between attributions and attachment.…”
Section: Attributions and Relationship Satisfactionmentioning
confidence: 99%
“…Given the substantial body of evidence that attributions are associated with relationship satisfaction, there is some confusion regarding underlying causes of specific attributions in romantic relationships. A number of researchers have demonstrated a link between adult attachment and attributions (Collins, Ford, Guichard, & Allard, ; Gardner, Busby, Burr, & Lyon, ; Mikulincer, , Study 2; Pearce & Halford, ). It is interesting that although Heene, Buysse, and Van Oost () found that attributions and adult attachment were linked to attributions and marital adjustment, they did not test whether attributions mediated the link between attributions and attachment.…”
Section: Attributions and Relationship Satisfactionmentioning
confidence: 99%
“…[and] are a significant part of what constitutes the fabric of the family functioning” (Dattilio, 2005, p. 15). Gardner, Busby, Burr, & Lyon (2011) found that when partners perceived poor marital relations in their family of origin, this negatively affected their attributions about their partner’s communication as well as the perceived kindness of the partners. Furthermore, healthy and supportive home environments shape important beliefs and attitudes about self, others, and relationships, including young adult relationships outside the family (Busby et al, 2005; Topham, Larson, & Holman, 2005).…”
Section: Predictors Of Partner Enhancementmentioning
confidence: 97%
“…As such, the consideration of cultural context will be relevant in this research study as well as clinical work with this population. In this study, the term family adversity reflects familial stressors and challenges researchers have found predictive of family dysfunction and negative romantic relational outcomes in adulthood for individuals who experienced these stressors in their FOO (Gardner, Busby, Burr, & Lyon, 2011; Holman & Busby, 2011). Examples of FOO stressors identified in previous literature, and assessed in this study include family members who struggle with alcohol or drug use, financial instability, emotional and mental health problems such as depression, and family members who struggle with physical disabilities or serious illness (Dagley, Sandberg, Busby, & Larson, 2012; Gardner et al, 2011; Grant et al, 2004).…”
Section: Background and Significancementioning
confidence: 99%